PERANAN PENERIMAAN PAJAK DAERAH TERHADAP PENDAPATAN ASLI DAERAH PADA CABANG PELAYANAN DINAS PENDAPATAN PROVINSI WILAYAH KABUPATEN BOGOR - sabil sabil (Universitas Bina Sarana Informatika, 2017)
To realize the goal of national development program that is just and prosperous society, needed development funds are not sedikit.untuk the local tax revenue is needed in sustainable regional development. local revenue component as Budget (APBD), which consists of revenue (PAD), Balance of funds, and other income, sah. This research method using qualitative methods of comparison, as well as literature. Based on the Local Tax receipts in 2011, 2012.2013, Realization is the value of money has increased when compared to the year 2011 (Rp. 622 389 004 003) to 2012 (Rp.751.189.702.605) difference of (Rp. 128 800 698 602), if comparison between 2012 (Rp751.189.702.605.) by the year 2013 (Rp. 964 731 885 667) the difference of (Rp.213.542.183.062), a total of out-on-year decline in percentage, in 2011 (128.63% ) compared to 2012 (123.00%), the difference of (5.63%), while the percentage comparison, in 2012 (123.00%) compared to 2013 (117.92%), the difference of (5.08%), overall the contribution of regional Tax on Revenue regions in 2011adalah 95%, while for 2012 the contribution of local Taxes on revenue is 99%, and for 2013 the contribution of local Taxes on revenue is 99%, see this figure menu njukkan that role Revenue of local taxes to the area is very significant compared with the filing of other sectors.